Spodoptera frugiperda J.E SMITH Attack on Non-Maize Crops in Bantul Regency - Putri, Tasya Triana; Putra, Ichsan Luqmana Indra (Universitas Ahmad Dahlan, 2023)
Spodoptera frugiperda is a polyphagous insect that has a main host of corn plants and attacks corn plants in the vegetative to generative phase. Besides corn, S. frugiperda has been reported to have other alternative host plants. The purpose of this study was to analyze the type of S. frugiperda attack most often found on alternative host plants and analyze the types of plants other than corn that are most often used as alternative hosts by S. frugiperda in Bantul Regency. This research was conducted in Bantul Regency in January-April 2023. Samples were taken from two villages from each sub-district in Bantul Regency. The research was conducted using survey method to determine the village as the research location and purposive method for sampling the alternative host plants. Samples taken were plants around corn fields with symptoms of S. frugiperda attack in the form of perforated leaves or traces of feces from feeding activities or S. frugiperda egg packages. The results of this study showed that 29 plant species from 13 families were attacked by S. frugiperda in Bantul Regency. The most common type of S. frugiperda attack was bite marks (60%). The most commonly attacked plant species came from the Poaceae family, namely elephant grass (Pennisetum purpureum). The conclusion of this study is that S. frugiperda has attacked plants other than corn in 17 sub-districts in Bantul Regency.